A comparative study of the extraction, transport and coordination chemistry of novel monotopic and ditopic salen-type ligands - Hensberg, Joshua Craig (Stellenbosch : Stellenbosch University, 2017)
Thesis (MSc)--Stellenbosch University, 2017.